KINERJA KEUANGAN DALAM MENGEVALUASI FINANCIAL DISTRESS PADA BANK YANG TERDAFTAR DI BEI - Wiwin Puspita sari; Faisal Abdullah; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2018)
Abstract This study aimsto determine the ratio of Likuiditas, solvabilitas and rentabilitas can be used in predicting financial distress in banking firms listed on the Indonesia stock exchange (IDX). The sample used in this study are listed banking companies in IDX during the observation period 2010-2014. The data analysis tool used is the CAEL ratio which includes Liquidity, Solvability and Rentability. CAEL ratio which includes Capital Adequancy Ratio (CAR), Debt to Total Asset Ratio, Return on Assets (ROA). The results of this study indicate that using CAEL ratios obtained 3 banks that did not experience Financial Distress namely Bank Rakyat Indonesia (Persero) Tbk, Bank Negara Indonesia (Persero) Tbk, and State Savings Bank (Persero) Tbk while those experiencing financial distress were only 1 Bank namely Bank Mandiri (Persero) Tbk. Bank Negara Indonesia Based on the table above, it is known that Bank Negara Indonesia for 5 years always receives a Z-Score ≥ 2.99 so that it is categorized as a Healthy company. This shows that the company always maintains the state of company performance. Bank Rakyat Indonesia Based on the table above it is known that Bank Rakyat Indonesia for 5 years always gets a Z-Score ≥ 2.99 so that it is categorized as a healthy company, this shows that the company always maintains the state of company performance. Bank Mandiri Based on the table above, it is known that Bank Mandiri for 5 years always gets a Z-Score 81 1.81 so that it is categorized as an unhealthy company (Financial Distress). State Savings Bank Based on the table above it is known that the State Savings Bank for 5 years always gets a Z-Score ≥ 2.99 so that it is categorized in a Healthy company. This shows that the company always maintains the state of company performanceKeywords : Financial Performance, Liquidity, Solvability, Rentability, Financial Distress